First Data on Ornithodoros moubata Aquaporins: Structural, Phylogenetic and Immunogenic Characterisation as Vaccine Targets - Ricardo Pérez-Sánchez; Ana Laura Cano-Argüelles; María González-Sánchez; Ana Oleaga (Pathogens, 2022)
Ornithodoros moubata transmits African swine fever and human relapsing fever in Africa. The elimination of O. moubata populations from anthropic environments is expected to improve the prevention and control of these diseases. Tick vaccines have emerged as a sustainable method for tick control, and tick aquaporins (AQPs) are promising targets for tick vaccines due to their vital functions, immunogenicity and ease of access by neutralising host antibodies. This study aimed at the systematic identification of the AQPs expressed by O. moubata (OmAQPs) and their characterisation as vaccine targets. Therefore, AQP coding sequences were recovered from available transcriptomic datasets, followed by PCR amplification, cloning, sequence verification and the analysis of the AQP protein structure and epitope exposure. Seven OmAQPs were identified and characterised: six were aquaglyceroporins, and one was a water-specific aquaporin. All of these were expressed in the salivary glands and midgut and only three in the coxal glands. Epitope exposure analysis identified three extracellular domains in each AQP, which concentrate overlapping B and T cell epitopes, making them interesting vaccine targets. Based on these domain sequences, a set of ten antigenic peptides was designed, which showed adequate properties to be produced and tested in pilot vaccine trials.